CRITICAL COMMUNICATIVE APPROACH IN THE VOCATIONAL SECONDARY EDUCATION - Kroiče, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The author investigates opportunities to apply critical communicative approach in the process of vocational training. To satisfy market demand for competitive and critically thinking experts it is necessary to provide problem oriented and reflexive training.The didactics of social constructivism is based on dialogical relations between teachers and trainees; mutual cooperation results in obtaining new experience, stimulation of cognitive activity, critical thinking and motivation.